Customs and Ceremonies of the Residents of the Surkhan Oasis Related to Marriage - Dustnazarova Mavzhuda Ilamonovna (International Journal on Integrated Education, 2022)
This article describes the wedding ceremonies and customs of the people of southern Uzbekistan. The article also analyzes the fact that the wedding ceremonies of the Surkhan oasis differed depending on the place of residence and living conditions of the population.